The Triumphal Echo of Psalm 24 in the Gospel According to Matthew - Carrier, Brian 1981- (2018)
This article argues for the presence of an echo from Psalm 24(23) in Matt 21,1-17 and discusses the implications that follow for reading the Matthean text. The echo, found in both lexical and thematic correlations between the two passages, is established using a methodology borrowed from Richard Hays. Its presence creates resonance with the Gospel's Christology and characterization and additionally strengthens the possibility that Mal 3,1 lies in the background of the Matthean triumphal entry account.